The ‘Danse Macabre’—Neutrophils the Interactive Partner Affecting Oral Cancer Outcomes - Hadjigol, Sara; Shah, Bansari A.; O’Brien-Simpson, Neil M. (Frontiers in Immunology, 2022)
Over the past few decades, tremendous advances in prevention, diagnosis, and treatment of cancers have taken place, however for Head and neck including oral cancer the overall survival rate is below 50% and they remain the seventh most common malignancies worldwide. These cancers are, commonly, aggressive, genetically complex, and difficult to treat and the delay which often occurs between early recognition of symptoms and diagnosis, and the start of treatment of these cancers is associated with poor prognosis. Cancer development and progression occurs in concert with alterations in the surrounding stroma with the immune system being an essential element in this process. Despite neutrophils having major roles in the pathology of many diseases, they were thought to have little impact on cancer development and progression. Recent studies are now challenging this notion and placing neutrophils as central interactive players with other immune cells and tumour cells in affecting cancer pathology. This review focusses on how neutrophils and their sub-phenotypes, N1, N2 and myeloid-derived suppressor cells both directly and indirectly affect the anti-tumour and pro-tumour immune responses. Emphasis is placed on what is currently known of the interaction of neutrophils with myeloid innate immune cells (such as, dendritic cells and macrophages), innate lymphoid cells, natural killer cells and fibroblasts to affect the tumour microenvironment and progression of oral cancer. A better understanding of the nature of this dialog will allow for improved therapeutics that concurrently target several components of the tumour microenvironment, increasing the possibility of constructive and positive outcomes for oral cancer patients. For this review PubMed, Web of Science and Google Scholar were searched for manuscripts using keywords and combinations thereof of “oral cancer, OSCC, neutrophils, TANs, MDSC, immune cells, head and neck cancer, tumour microenvironment” with a focus on publications from 2018 to 2021.